1998
DOI: 10.4315/0362-028x-61.10.1312
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Counting of Viable Bacteria in Vegetables and Environmental Water Using a Photon-Counting TV Camera

Abstract: A bioluminescence assay carried out with a photon-counting TV camera was evaluated for rapid enumeration of viable bacterial counts. The test sample was filtered through a membrane filter, and the membrane filter retaining bacteria was incubated at 37 degrees C for 6 h on a filter paper soaked with nutrient broth supplemented with 0.5% NaCl. The membrane filter was then subjected to a bioluminescence reaction, and the intensity of light and numbers of light emission points on the filter were measured with a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…(iii) The kinetic methods did not need sophisticated apparatus. Miyamoto et al 21) reported a method for bacterial cell counts with a photon-counting TV camera, which was based on firefly bioluminescence. There is also a commercially available system of microbial cell counting with a similar camera system (MicroStar TM -RMDS, Millipore Corp.).…”
Section: Discussionmentioning
confidence: 99%
“…(iii) The kinetic methods did not need sophisticated apparatus. Miyamoto et al 21) reported a method for bacterial cell counts with a photon-counting TV camera, which was based on firefly bioluminescence. There is also a commercially available system of microbial cell counting with a similar camera system (MicroStar TM -RMDS, Millipore Corp.).…”
Section: Discussionmentioning
confidence: 99%
“…Microbes represent an excellent source proteases due to their broad biochemical diversity (Godfrey & West,1996), their rapid growth, the limited space and the low cost that growing substrates required for their cultivation (Gupta et al, 2002). Vegetables are renewable raw materials associated with diverse microbial populations (Gó mez, Muñ oz, de Ancos, & Cano, 2002;Miyamoto et al, 1998;Ponce, Moreira, del Valle, & Roura, 2008), therefore they could be an interesting and cheap source of proteolytic bacteria. Among vegetables cabbage (Brassica oleracea var capitata) is a biennial sturdy and inexpensive leafy plant.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a simple, rapid, and accurate detection method is desirable. Several non-culture methods have been used for the rapid detection of bacteria in food (Fujikawa and Morozuki, 2003;Gracias and Mckillip, 2004;Kawasaki et al, 2004;Kawasaki et al, 2007;Masuda-Nishimura et al, 2000;Miyamoto et al, 1998). PCR is a useful technique because of its high sensitivity.…”
Section: Introductionmentioning
confidence: 99%